Sentence, Utterance, and Presupposition in Charles Dickens’ A Child’s Dream of A Star - Amanda Ravinska Syaira; Annisa Yumna Maharani2; Callysta Feodora Laiskodat; Kayla Nadine Putri Azra (INDO PUBLISHING, 2025)
This analysis reveals that Dickens’ A Child’s Dream of a Star employs a rich mix of sentence types and pragmatic cues to convey its themes. The literal meaning of each sentence (semantic content) is often clear, but the full meaning arises only when utterance context and presuppositions are taken into account. Declarative sentences ground the narrative, interrogatives express longing or speculation, and exclamations/imperatives heighten emotion. Presuppositions – the assumptions characters take for granted – shape how readers understand the familial and spiritual context. For instance, the repeated use of “Is my brother come?” presupposes a belief in life after death and familial reunion, driving the story’s emotional arc. The study underscores that even in a literary text, formal semantics and pragmatic theory are both needed to explain how meaning is constructed. By tabulating sentence, utterance, and presupposition features, we see the interplay between grammatical form and inferred content. These insights have implications for semantics research: they show that narrative language engages everyday presuppositions and speech-act conventions, and that analyzing such texts can illustrate how speakers use language creatively yet systematically. Further work could apply similar analyses to other literary works, or investigate reader interpretations of presupposed content.